Handbook of poverty in India perspectives, policies, and programmes - Radhakrishna R; Roy Shovan (Oxford OUP, 2005)
The volume provides an account of the incidence, trends, and determinants of poverty in India and reviews the situation in the context of deprivations, empowerment, role of poor in governance, its geographical concentration, major policies and programme
Keywords: India; Poverty